Reovirus infection induces stabilization and up-regulation of cellular transcripts that encode regulators of TGF-β signaling - Guo, Liang (PLoS One, 2018)
Reovirus infection induces dramatic changes in host mRNA expression. We utilized oligonucleotide microarrays to measure cellular mRNA decay rates in mock- or reovirus-infected murine L929 cells to determine if changes in host mRNA expression are a consequence of reovirus-induced alterations in cellular mRNA stability. Our analysis detected a subset of cellular transcripts that were coordinately induced and stabilized following infection with the reovirus isolates c87 and c8, strains that led to an inhibition of cellular translation, but not following infection with Dearing, a reovirus isolate that did not negatively impact cellular translation. The induced and stabilized transcripts encode multiple regulators of TGF- β signaling, including components of the Smad signaling network and apoptosis/survival pathways. The coordinate induction, through mRNA stabilization, of multiple genes that encode components of TGF-β signaling pathways represents a novel mechanism by which the host cell responds to reovirus infection.